Implementasi Konsep Pendidikan Perspektif Imam Al-Ghazali Pada Siswa Inklusi di Sekolah Menengah Pertama Sunan Ampel Jombang - Zulfah, Machnunah Ani; Abadi, Sendy Chandiawan; Roziqin, Muhamad Khoirur (JoEMS (Journal of Education and Management Studies), 2023)
The concept of education is one of the important components in the education system, considering that the definition of education itself is a process that definitely has goals to be achieved. In this case the problem is for inclusive students who participate in regular student education because there should be differences in the teaching tools. This study uses a qualitative approach that tends to be a descriptive research method. The process of controlling the data used interviews with the teachers and observing teaching and learning activities at SMP Sunan Ampel Jombang. The study shows that the educational management at Sunan Ampel Jombang Middle School is different from other schools, because at Sunan Ampel Middle School there are inclusive students.